Leibniz’s and Spinoza’s supposed critique of the Cartesian ‘picture-idea’ - Teixeira, William de Jesus (Sofia, 2023)
This paper’s aim is to try to answer the critique made by some Leibniz’s and Spinoza’s scholars against Descartes’s ‘idea-picture’. In the first part of this paper, I put forward Leibniz’s and Spinoza’s scholars arguments issued in order to criticize the Cartesian idea-picture. In the second part, I expose the reasons why I believe that it is possible to reject the critique of these scholars against the idea-picture. In my view, there are three fundamental elements which support my thesis: the sound comprehension of the expression idea tanquam rerum imagines, the Cartesian theory of ‘causal dissimilarity’ between the object of perception and the sensations brought about by it, and Descartes’ theory of innateness.